Research updates on graphene oxide‐based polymeric nanocomposites. Issue 12 (30th January 2014) - Maheshkumar, K.V.; Krishnamurthy, K.; Sathishkumar, P.; Sahoo, S.; Uddin, E.; Pal, S.K.; Rajasekar, R.
<x xml:space="preserve">Abstract</x> Graphene oxide (GO) is a carbon‐based material, which is one atom thick sheet of graphite. The nanofillers have exceptional stiffness and strength owing to the presence of two‐dimensional graphene backbone. Especially owing to this reason, nanocomposites have been developed using GO for several applications. This review article explores the synthesis of GO from flake graphite. Main emphasis has been afforded on the preparation and characterization of GO nanocomposites, utilizing various industrial polymers for wide application in aerospace, biomedical, military, supercapacitors, electrical, sensor, and so on. Morphological characterization exploring the interaction and extent of dispersion of GO nanosheets in the polymer matrices is extensively accounted. From the reports, it is clear that exfoliation and strong interaction of GO tremendously improved the physical, mechanical, thermal, electrochemical, biocompatibility, and tribological properties of the added polymer. POLYM. COMPOS., 35:2297–2310, 2014. © 2014 Society of Plastics Engineers